Design and Development of a Fisherman's Trap Location Marking Application Using Android-Based Maps Picker and Tracking - Kuswanto, Teguh Junian; Hamka, M. Saiful Rahman; Febrianti, Santi; Rokhim, Imam Nur; Nabila, Aisyah Nur (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The fisheries sector in Indonesia is predominantly composed of small-scale traditional fishermen who still rely on manual methods to determine and track the locations of fishing gear, such as fish traps (bubu). This condition often leads to the loss of fishing gear due to environmental factors such as weather conditions, ocean currents, and limited access to modern navigation technologies. Therefore, there is a need for an information technology–based solution that can assist fishermen in digitally marking and tracking the locations of their fishing gear. This study aims to design and develop an Android-based application capable of marking and tracking the deployment locations of fish traps using a Maps Picker and Global Positioning System (GPS) in real time. The system development adopts the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and evaluation phases. The application is developed using React Native as the primary framework, integrated with the Google Maps API and SQLite as a local database to support offline-first functionality. System testing is conducted using a black-box testing approach. The results indicate that all application features function according to the specified requirements and demonstrate a satisfactory level of tracking accuracy. Therefore, the proposed system is considered effective in assisting fishermen in marking and tracking fishing gear locations efficiently, while also supporting the digital transformation of the small-scale fisheries sector in Indonesia.